2015
DOI: 10.2166/wh.2015.268
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium and Giardia in recreational water in Belgium

Abstract: The objective of this study was to investigate the presence of Cryptosporidium and Giardia in different recreational water bodies in Belgium and to estimate the infection risk associated with swimming and other recreational activities. Cryptosporidium oocysts and/or Giardia cysts were detected in three out of 37 swimming pools, seven out of 10 recreational lakes, two out of seven splash parks and four out of 16 water fountains. In the swimming pools no infection risk for Cryptosporidium could be calculated, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…Given the epidemiological characteristics of swimming pools observed in this study (Table 1) the positivity results for Giardia cysts (19%) and Cryptosporidium oocysts (9.5%) determined by IFA were not surprising. In Belgium, Ehsan et al (2015) found that three out of 37 swimming pool samples (8.1%) tested positive for Cryptosporidium, Giardia or both protozoa. In the USA, Shields, Gleim, and Beach (2008) sampled 160 swimming pools not associated with outbreaks and found that 13 (8.1%) were positive for one or both parasites, ten (6.2%) for Giardia cysts, two (1.2%) for Cryptosporidium oocysts and one (0.6%) for both parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Given the epidemiological characteristics of swimming pools observed in this study (Table 1) the positivity results for Giardia cysts (19%) and Cryptosporidium oocysts (9.5%) determined by IFA were not surprising. In Belgium, Ehsan et al (2015) found that three out of 37 swimming pool samples (8.1%) tested positive for Cryptosporidium, Giardia or both protozoa. In the USA, Shields, Gleim, and Beach (2008) sampled 160 swimming pools not associated with outbreaks and found that 13 (8.1%) were positive for one or both parasites, ten (6.2%) for Giardia cysts, two (1.2%) for Cryptosporidium oocysts and one (0.6%) for both parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Most AGI outbreaks in treated recreational water are associated with ingesting Cryptosporidium . Cryptosporidium has been detected in treated recreational water and associated with outbreaks internationally [ 5 , 6 , 7 , 8 ]. From 2000–2014, Cryptosporidium caused 58% of treated recreational water outbreaks in the U.S. [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…1). Despite much lower numbers being examined, the positivity rate for Giardia was higher than Cryptosporidium in 10 of the laboratories (ID 1, 4, 5, 9, 12, 14, 15,16,18,19) where the percentage positivity for Giardia ranging from 0% to 3•71% ( Fig. 2) with 166 laboratoryconfirmed cases.…”
mentioning
confidence: 95%
“…For Cryptosporidium, the majority of laboratories (17/19) performed microscopy to detect oocysts. The most common staining method chosen was AP confirmed by mZN in eight laboratories (ID 1, 3, 5-7, 11,16,19). Three laboratories performed mZN alone (ID 9, 14, 18), six employed AP staining only (ID 4, 8, 10, 12, 13, 15), one laboratory used a lateral flow immunochromatographic antigen assay (ID17), and another performed a manually washed plate-based EIA (ID 2).…”
mentioning
confidence: 99%